2011
DOI: 10.1634/theoncologist.2010-0349
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Member of the BCL2 Gene Family, BCL2L12, Is Substantially Elevated in Chronic Lymphocytic Leukemia Patients, Supporting Its Value As a Significant Biomarker

Abstract: BCL2L12 is a recently identified gene belonging to the BCL2 family, members of which are implicated in hematologic malignancies, including chronic lymphocytic leukemia (CLL). The aim of this study was to analyze the mRNA expression of the novel apoptosis-related gene BCL2L12 in patients with CLL and to examine its prognostic and predictive value and potential clinical application as a novel molecular biomarker for CLL. For this purpose, total RNA was isolated from peripheral blood of 65 CLL patients and 23 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 77 publications
(112 reference statements)
0
16
0
2
Order By: Relevance
“…To evaluate the performance of network biomarkers in classifying leukemia and normal gene expression profiles, we used three independent gene expression datasets listed in Table 3 as tested datasets to produce the ROC curves. We compared the network biomarker with three reported gene biomarkers: CD38 47 , BCL2 48 and IGFBP7 49 . The reasons we chose these three markers for comparison are as follows, 1) these biomarkers are all well-studied and all of them have been validated by clinical experiments.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the performance of network biomarkers in classifying leukemia and normal gene expression profiles, we used three independent gene expression datasets listed in Table 3 as tested datasets to produce the ROC curves. We compared the network biomarker with three reported gene biomarkers: CD38 47 , BCL2 48 and IGFBP7 49 . The reasons we chose these three markers for comparison are as follows, 1) these biomarkers are all well-studied and all of them have been validated by clinical experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we also showed that BCL2L12 mRNA is dramatically elevated in CLL patients, in comparison with healthy controls. Interestingly, BCL2L12 mRNA expression was found to possess significant discriminatory value in CLL, distinguishing very efficiently CLL patients from non-leukemic population, and to constitute an unfavorable prognostic biomarker in CLL, in terms of overall survival (Papageorgiou et al, 2011).…”
Section: Efmentioning
confidence: 99%
“…Following the manufacturer's instructions, total RNA was extracted and diluted in a RNA Storage Solution (Ambion Europe Ltd.) and stored at )80°C until use. First-strand cDNA was then synthesized using the M-MuLV Reverse Transcriptase, RNase H ) (Finnzymes Oy, Vantaa, Finland), RNaseOUTÔ RNase inhibitor (Invitrogen, Carlsbad, CA, USA) and oligo(dT) [12][13][14][15][16][17][18] as primer, according to the manufacturer's instructions.…”
Section: First-strand Cdna Synthesismentioning
confidence: 99%